Odpowiedź :
Odpowiedź:
1)
[tex](3t - 7)(t - 2) = {3t}^{2} - 13t + 14 = [/tex]
[tex]t = \frac{1}{3} [/tex]
[tex]3 \times ( \frac{1}{3} )^{2} - 13 \times \frac{1}{3} + 14 =[/tex]
[tex]3 \times \frac{1}{9} - \frac{13}{3} + 14 = \frac{1}{3} - \frac{13}{3} + \frac{42}{3} = [/tex]
[tex] \frac{30}{3} = 10[/tex]
2)
[tex](xy - x)(3xy + 5x) = [/tex]
[tex] = {3x}^{2}{y}^{2} + 5 {x}^{2} y - 3 {x}^{2} y - 5 {x}^{2} = [/tex]
[tex] = 3 {x}^{2} {y}^{2} + 2 {x}^{2} y - 5 {x}^{2} [/tex]
[tex]y = - 1.3[/tex]
[tex]3 {x}^{2} ( - 1.3)^{2} + 2{x}^{2} ( - 1.3) - {5x}^{2} = [/tex]
[tex] = {3x}^{2} \times 1.69 + {2x}^{2} \times ( - 1.3) - {5x}^{2} = [/tex]
[tex] = 5.07{x}^{2} - 2.6{x}^{2} - {5x}^{2} = - 2.53{x}^{2} [/tex]